CONTROL OF ILLEGAL MINING (PETI) IN INDONESIA: POLICY AND PROGRAM - UKAR W. SOELISTIJO (Puslitbang tekMIRA, 2011)
The activity program of illegal mining prevention and tackling which constitutes non-formal enterprise and employing job within the outlying regions becomes as part of the regional development program in which may include community development program as well. Community development in the sector of energy and mineral resources is the program of community empowerment including the community of illegal mining (PETI) is directed toward self-sustainability in the enterprise in lieu of the order of formal enterprise and employing job. The management handling of illegal mining prevention and tackling program may include the components of identification of the PETI causal factors, the system of registering and mapping PETI distribution, the system of state financial loss estimation (fiscal and non-fiscal), mapping PETI players, mapping organiza- tion related to the development and supervision of PETI including its type of job and function, system of PETI prevention, tackling system of PETI impacts, systematization of the effort of PETI prevention and tackling. Successfulness indicator of PETI prevention and tackling may include the progressive and active response of PETI players and the sustainability in terms of social-economics, human and environment as well. The implementation of PETI prevention and tackling faces various challenges and opportunities which should be anticipated. Whatever in the living circle of the people human-being is based on the philosophy of eager to live in the right track in term of law enforcement or legal. At one time, the living of PETI must be left which functions presently as temporary economic safety valve even with very high risk, while formal job has not been yet found out. Somehow, the government has moral responsibility to make the people alive by creating good quality of enterprise and job. The effort of PETI curb is expected to be able to carry out systematically, well- planned and well-directed up to the whole and entire goal is well reached for the shake of nation and state glory and prosperity.